2014
DOI: 10.1080/10615806.2014.968563
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and emotional responses to subjective social evaluative threat in daily life

Abstract: This research suggests an important role for anxiety, embarrassment, and shame as emotional consequences of naturally occurring evaluative threat, especially for those who are more socially anxious. Further, this work replicates other naturalistic studies that have documented increased blood pressure at times of SSET and extends that work by documenting cardiovascular responses into the following hour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Our findings are, for instance, in concordance with studies of the pathogenic impact of perseverative cognition, ruminations and worries 39. Correspondingly, low self-esteem,40 unfairness,41 lack of well-being,25 42 work dissatisfaction,43 loneliness,44 lack of social relationships,45 subjective social–evaluative threat46 and anger47 have been related to impaired health. A perceived lack of purpose in life has recently been connected to allostatic load,48 49 as has compromised sleep quality 50–52…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are, for instance, in concordance with studies of the pathogenic impact of perseverative cognition, ruminations and worries 39. Correspondingly, low self-esteem,40 unfairness,41 lack of well-being,25 42 work dissatisfaction,43 loneliness,44 lack of social relationships,45 subjective social–evaluative threat46 and anger47 have been related to impaired health. A perceived lack of purpose in life has recently been connected to allostatic load,48 49 as has compromised sleep quality 50–52…”
Section: Discussionsupporting
confidence: 90%
“…Within the SET model, the social emotion of shame is believed to play a prominent role in orchestrating exaggerated physiological responses that are specific to social contexts (Dickerson, Kemeny, Aziz, Kim, & Fahey, 2004). A series of recent experience sampling studies have demonstrated that SET in daily life is associated with heightened cardiovascular responding (e.g., Lehman, Cane, Tallon, & Smith, 2014).…”
Section: Relationships and Health: A Review Of The Theoriesmentioning
confidence: 99%
“…A series of recent experience sampling studies have demonstrated that SET in daily life is associated with heighted cardiovascular responding (e.g., Lehman, Cane, Tallon, & Smith, 2014).…”
Section: Relationships Affect and Health 15mentioning
confidence: 99%
“…Our screening results identified three different types of cardiovascular measures: blood pressure, heart rate, and heart rate variability. Blood pressure was assessed in 19 reports [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] (Table 2), heart rate in 21 studies [37-39, 42, 43, 45-47, 51, 53, 56-66] (Table 3), and heart rate variability in 12 studies [56,58,59,62,64,65,[67][68][69][70][71][72] (Table 4). Specifically, BP was measured as systolic (SBP) or diastolic (DBP) blood pressure, mean arterial pressure (MAP), or pulse pressure (PP).…”
Section: Study Characteristicsmentioning
confidence: 99%